Pedagogical Collaboration for Multilingual Support in Swedish Compulsory Schools: Mother Tongue Teachers’ perspectives - Roux Sparreskog, Christa (Educare, 2023)
The present study analyses mother tongue teachers’ perspectives on pedagogical collaboration for multilingual support with two specific groups of professionals: mainstream teachers and special educational needs teachers (SEN). Furthermore, it discusses what factors influence the described pedagogical collaboration. A purposeful sampling with a maximum variation was chosen to obtain the highest possible representativeness. Thereafter, 13 individual, thematical, open-structured interviews were conducted. To analyse the themes arising from the abductive analysis of the interviews, Bronstein’s (2003) theoretical model for interdisciplinary collaboration was used. The results show that mother tongue teachers mostly collaborate with mainstream teachers and SEN teachers to solve structural and administrative issues and to share competence and knowledge. Further, the analysis of the influencing factors on the pedagogical collaboration shows that although mother tongue teachers have a firm and consistent perception of their professional role, structural characteristics hinder naturally occurring collaboration. Limited informal contact and the lack of mainstream teachers’ and SEN teachers’ experiences of successful pedagogical collaboration for multilingual support affect their willingness to collaborate with mother tongue teachers. Therefore, the findings suggest that valuable multilingual resources would be made better use of when structural and administrative matters are formalized.